A Reactive Location Routing Algorithm with Cluster-Based Flooding for Inter- Vehicle Communication - Raúl Aquino S. (Computación y Sistemas, 2006)
In this paper, we present a reactive location routing algorithm with cluster-based flooding for inter-vehiclecommunication. We consider a motorway environment with associated high mobility and compare position-basedand non-position-based routing strategies, along with a limiting function for flooding mechanisms in reactive ad-hocprotocols. The performance of Dynamic Source Routing (DSR) and Ad-Hoc On-demand Distance Vector Routing(AODV) for non-positional and Location Routing Algorithm with Cluster-Based Flooding (LORA_CBF) forpositional algorithms is considered. First, for small-scale networks, our research validates our proposed simulationmodel with the results of a test bed and the results of mathematical analysis. Then, for large-scale networks, we usesimulations to compare our model with both the AODV and DSR reactive routing algorithms. Finally, we use amicroscopic traffic model, developed in OPNET, to ascertain the mobility of 250 vehicles on a motorway withregards to average Route Discovery (RD) time, End-to-End Delay (EED), Routing Load, Routing Overhead,Overhead, and Delivery Ratio.